Investigating the Effects of Location-Based Advertising in the Supermarket: Does Goal Congruence Trump Location Congruence?. Issue 1 (2nd January 2016) - van 't Riet, Jonathan; Hühn, Arief; Ketelaar, Paul; Khan, Vassilis-Javed; Konig, Ruben; Rozendaal, Esther; Markopoulos, Panos
ABSTRACT: Advertising professionals have great expectations for location-based advertising (LBA). The present study therefore set out to investigate whether ads that are tailored to consumers' location are indeed more effective than ads that are not. In addition, it was investigated whether LBA is particularly likely to be effective when the ad is not only location congruent but also relevant to consumers' goals. Therefore, a 2 (location congruence) × 2 (goal relevance) experimental design was employed. These expectations were borne out: the location-congruent ad resulted in more purchases than the location-incongruent ad, but only when the ad was high in goal relevance. These results suggest that it is profitable for advertisers to send "local" messages only when these messages are relevant.